2020
DOI: 10.1111/jcmm.16198
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and pre‐hospitalization use of low‐dose aspirin in COVID‐19 patients with coronary artery disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 30 publications
3
60
1
2
Order By: Relevance
“…(Lima-Morales et al, 2021) There were 6 eligible studies that were included in this meta-analysis, comprising of 13,993 patients [Figure 1]. (Jonathan H. Chow et al, 2021;Liu et al, 2021;Meizlish et al, 2021;Merzon et al, 2021;Osborne et al, 2021;Yuan et al,…”
mentioning
confidence: 99%
“…(Lima-Morales et al, 2021) There were 6 eligible studies that were included in this meta-analysis, comprising of 13,993 patients [Figure 1]. (Jonathan H. Chow et al, 2021;Liu et al, 2021;Meizlish et al, 2021;Merzon et al, 2021;Osborne et al, 2021;Yuan et al,…”
mentioning
confidence: 99%
“…Treatment with low dose ASA for coronary artery disease, atrial fibrillation, or stroke prophylaxis confers COVID-19 protection as observed in retrospective studies [ 130 , 131 , 132 ]. Patients already on low dose ASA and having COVID-19 were significantly less likely to require admission to the intensive care unit or require use of a mechanical ventilator, and more likely to survive than patients not on ASA [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients already on low dose ASA and having COVID-19 were significantly less likely to require admission to the intensive care unit or require use of a mechanical ventilator, and more likely to survive than patients not on ASA [ 130 ]. Based on studies specific to SARS-CoV-2, in both the prophylactic antiviral effects and effects in the treatment using ASA 75 mg po daily has been reported [ 130 , 131 , 132 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 18 A recent retrospective cohort study revealed that prehospital aspirin use in hospitalised patients with COVID-19 with established coronary artery disease was not associated with increased all-cause mortality. 45…”
Section: Secondary Prevention Of Arterial Thrombosis During Covid-19 Pandemicmentioning
confidence: 99%